1974
DOI: 10.2307/1934413
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing Forest History from Live and Dead Plant Material‐‐An Approach to the Study of Forest Succession in Southwest New Hampshire

Abstract: The purpose of this study is to see if it is possible to determine the course of forest succession over several hundred years by the dissection and close scrutiny of live and dead plant material. The study area was a one-tenth-acre (0.04-ha) square plot in a forest that had never been cut, located near Ashuelot in southwestern New Hampshire. Within it stem-location and growth-rate data were collected from three different classes of stems: 1) living trees, 2), dead unburied stems and stem fragments, and 3), woo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
244
0
3

Year Published

1981
1981
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 408 publications
(255 citation statements)
references
References 32 publications
(26 reference statements)
5
244
0
3
Order By: Relevance
“…It is a common, but rarely dominant, overstory species. Although it is recognized as a mound specialist in hurricane gaps (Henry and Swan 1974), B. lenta was able to grow into the canopy from both established seedlings and new seedlings on all microenvironments. Its importance may decline as the forest further develops; however, Motzkin et al (1999) found that 1938 hurricane damage had a strong positive influence on overstory B. lenta importance more than 50 years after the storm.…”
Section: Survivors Control the Regeneration Processmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a common, but rarely dominant, overstory species. Although it is recognized as a mound specialist in hurricane gaps (Henry and Swan 1974), B. lenta was able to grow into the canopy from both established seedlings and new seedlings on all microenvironments. Its importance may decline as the forest further develops; however, Motzkin et al (1999) found that 1938 hurricane damage had a strong positive influence on overstory B. lenta importance more than 50 years after the storm.…”
Section: Survivors Control the Regeneration Processmentioning
confidence: 99%
“…For example, in New England, hypotheses of the role of windstorms in structuring forest dynamics are strongly influenced by studies of the 1938 ''Great Hurricane.'' Like many studies of disturbance, research on the 1938 hurricane lacked both controls and systematic beforeand-after measurements (Rowlands 1941, Foster 1988a, b, Merrens and Peart 1992 and emphasized immediate impacts and intermittent multi-decadal sampling rather than continuous trajectories (cf., Spurr 1956, Henry and Swan 1974, Mabry and Korsgren 1998. Such studies may miss critical stages in recovery, such as regeneration and the mechanisms involved, or short-lived episodes of rapid growth or population expansion.…”
Section: Introductionmentioning
confidence: 99%
“…Alors que les structures régulières dominent dans la pessière de l'ouest, ce sont clairement les peuplements irréguliers qui sont majoritaires dans la pessière de l'est. On attribue généralement la structure irrégulière aux vieux peuplements (Henry et Swan 1974), plus particulièrement aux peuplements inéqui-ennes (Groot et Horton 1994, Smith et al 1997, Linder 1998, contrairement à la structure régulière qui caractériserait davantage les peuplements jeunes et équiennes (Baker 1923, Meyer 1930, Hough 1932, Mohler et al 1978, Smith et al 1997. On reconnaît en fait que la structure diamétrale est amenée à changer avec le temps écoulé depuis le dernier feu (Knowles et Grant 1983, Lorimer et Krug 1983, Groot et Horton 1994, Linder 1998.…”
Section: Comparaison Entre La Pessière De L'est Et La Pessière De L'ounclassified
“…Fire is also a major force in generating disturbance in temperate forests (Heinselman 1973, Taylor 1973), although fire-generated disturbance will have many properties distinct from those of our system. Tornado and hurricane destructions are known to be important in both temperate (Turner 1935, Henry andSwan 1974) and tropical (Whitmore 1974) forests, generating larger scale gaps. Earthquakes and the accompanying landslides produce comparable forest destruction (Veblen andAshton 1978, Garwood et al 1979).…”
Section: Within-patch Replacement: a Generalized Sequencementioning
confidence: 99%